2012
DOI: 10.1002/anie.201204066
|View full text |Cite
|
Sign up to set email alerts
|

An Air‐Stable Low‐Bandgap n‐Type Organic Polymer Semiconductor Exhibiting Selective Solubility in Perfluorinated Solvents

Abstract: A thin‐film transistor: An n‐type polymer semiconductor, poly(2,3‐bis(perfluorohexyl)thieno[3,4‐b]pyrazine), was synthesized through a Pd‐catalyzed polycondensation employing a perfluorinated multiphase solvent system. This is the first example of an n‐type polymer semiconductor with exclusive solubility in fluorinated solvents. The fabrication of organic field effect transistors containing this new n‐type polymer semiconductor is shown (see picture).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 68 publications
1
47
0
Order By: Relevance
“…Polymer semiconductors are receiving considerable attention in fundamental science and applied research owing to their potential for application in various electronic devices, [1,2] such as organic thin-film transistors (OTFTs) [3][4][5] and polymer solar cells (PSCs). [6,7] In the last decade,agreat number of ptype polymers with promising OTFT [2,8] and PSC [9,10] performance have been synthesized.…”
mentioning
confidence: 99%
“…Polymer semiconductors are receiving considerable attention in fundamental science and applied research owing to their potential for application in various electronic devices, [1,2] such as organic thin-film transistors (OTFTs) [3][4][5] and polymer solar cells (PSCs). [6,7] In the last decade,agreat number of ptype polymers with promising OTFT [2,8] and PSC [9,10] performance have been synthesized.…”
mentioning
confidence: 99%
“…In addition, the strong electronegativity might induce F-S and F-H interactions and potentially modifies the molecular conformation and intermolecular organization (6). Furthermore, it has been shown that fluorination often leads to enhanced thermal and oxidative stability (9)(10)(11). Given a combination of these desirable properties, fluorine-containing CPs have led to most of the best-performing polymer-based solar cells to date (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…On the contrary, F atom can significantly enhance the non‐covalent interactions through F‐F, F‐C, F‐O, F‐S or F‐H etc. among the molecules . Such interactions can push F‐containing molecules more closely packed and facilitate effective energy transfer and charge transport in the films .…”
Section: Methodsmentioning
confidence: 99%